Marburg Virus Disease: Latest Outbreak and Current Research Review - Ramdas Bhat,; Preeti Shanbhag, (Indian Journal of Pharmacy & Drug Studies, 2024)
The Marburg virus disease (MVD) is a severe and deadly viral hemorrhagic fever caused by the Marburg virus. Recent outbreaks have raised global concerns due to the severity of the disease, high mortality rate, and limited treatment options. This review provides an overview of the latest outbreak and current research on MVD, including efforts to understand the virus's epidemiology, transmission, pathogenesis, and diagnosis, as well as the development of antiviral therapies and vaccines. Advances in diagnostic techniques and experimental antiviral drugs show promising results. However, controlling outbreaks remains challenging due to various factors such as limited access to affected areas, inadequate healthcare infrastructure, and community resistance to interventions. Therefore, a multidisciplinary approach involving public health measures, clinical care, and research efforts is crucial in mitigating the impact of MVD outbreaks and improving patient outcomes. Further research and collaborative efforts are needed to develop effective strategies for preventing and managing MVD and protecting public health.